Tumor aggregates from ovarian cancer patients ascitic fluid present low caspase-3 expression - Batista-Pinto , C.; Resende, A. D.; Andrade, R.; Garcez, F.; Ferreira , V.; Lobo, C.; Monteiro , P.; Abreu , M. H.; Bartosch, C.; Ricardo , S. (Scientific Letters, 2023)
Background: Ascites is observed in ovarian cancer advanced stages because of the inflammatory process caused by tumor cells invasion of the peritoneal cavity [1,2]. In the ascitic fluid microenvironment, tumor cells can be found isolated or forming aggregates, being key mediators of transceolomic metastization [1,2]. In vitro multicellular spheroids show anoikis resistance presenting high survival levels when compared to isolated tumor cells [3]. The viability of these tumor cells is crucial for the establishment of patient-derived organoids (PDOs) that constitute a valuable preclinical platform for drug testing [3]. Objective: This study aims to evaluate the tumor cells apoptotic levels (single cells and aggregates) in the ascitic fluid of ovarian cancer patients. Methods: We evaluated 23 cytologic samples from ovarian cancer patients with ascites admitted at IPOPorto under a project approved by IPOPorto ethics committee (CES.092R1/019). Standard histologic processing was performed on the formalin-fixed and Histogel™ embedded ascitic fluid. For the apoptotic cell detection an immunohistochemistry technique with anti-caspase-3 antibody was applied and evaluated by microscopy. Results: During standardization, the ideal primary antibody concentration and incubation time were set, as also the antigenic retrieval procedure was optimized. We included a positive control to validate the technique in each run. Our results show that, in most of the samples, cellular aggregates were negative for caspase-3 expression, >75% of the cells, but some positivity was observed in isolated tumor cells. Conclusions: The evaluation of caspase-3 expression by immunohistochemistry proved to be a reliable methodology to evaluate the apoptotic levels in cytology samples. In general, tumor cells within aggregates showed high viability levels, whereas some isolated tumor cells presented caspase-3 expression, which indicate they are undergoing an apoptotic process. The tumor aggregates high viability in these samples is a good indicator that the establishment of PDOs from these tumor cells will be successful.